2000
DOI: 10.3989/cyv.2000.v39.i6.769
|View full text |Cite
|
Sign up to set email alerts
|

Recubrimientos sol-gel obtenidos por deposición electroforética (EPD) sobre metales

Abstract: El proceso sol-gel es un método de gran interés para la producción de películas vítreas sobre metales, que actúan como barrera protectora frente a la oxidación y aumentan su resistencia a la corrosión. Se han obtenido recubrimientos inorgánicos e híbridos de distintas composiciones sobre distintos metales usando técnicas como inmersión, centrifugado y pulverización. Aunque estos métodos proporcionan recubrimientos con buenas propiedades los espesores obtenidos son bajos (inferiores a 2 mm), lo que limita sus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The incorporation of other silica precursors as methyl triethoxysilane (MTES) that presents an organic radical that remains in the final structure, improves the process, also enhancing the flexibility and avoiding the appearance of cracks in SG materials. This synthesis has been widely used in sol-gel coatings with the aim to increase the thin films thickness [20,21].…”
mentioning
confidence: 99%
“…The incorporation of other silica precursors as methyl triethoxysilane (MTES) that presents an organic radical that remains in the final structure, improves the process, also enhancing the flexibility and avoiding the appearance of cracks in SG materials. This synthesis has been widely used in sol-gel coatings with the aim to increase the thin films thickness [20,21].…”
mentioning
confidence: 99%
“…[4,20] The strong conditions imposed by basic catalysis of TMES/TEOS promotes the development of a particulate structure of nano-sized particles, whose concentration depends on the final dilution. Since the isoelectric point of silica in water typically lies at »pH 2, the particles dispersed at pH 9±10 are expected to be negatively charged at the surface and so they should migrate towards the anode, to produce an anodic deposition.…”
mentioning
confidence: 99%
“…ZrO 2 -SiO 2 -Na 2 O sols have been prepared under similar basic conditions to those outlined above, which also generated particulate structures. 25,37 These sols were prepared in two steps, prehydrolysis of MTES and TEOS with NaOH, followed by addition of zirconium alkoxide (zirconium(IV) butoxide) complexed with acetyl acetone (AcAc) and water to complete the hydrolysis reaction. The viscosity and stability of these particulate sols were strongly affected by the H 2 O/ (MTESzTEOS) ratio and the total amount of NaOH.…”
Section: Synthesis By Basic Catalysismentioning
confidence: 99%
“…Rheological measurements showed that these sols exhibited Newtonian behaviour with a viscosity of 2-4 mPa s, depending on the particle concentration. 41 No critical limit was observed in production of films by dipping, up to thicknesses of 4 mm. SiO 2 -ZrO 2 sols from ZrO 2 colloidal suspensions (Nyacol, 20%ZrO 2 , pH 10, particle size 5-10 nm) were obtained by the same procedure, although these were characterised by lower ZrO 2 concentrations, owing to greater dilution of the colloidal suspension.…”
Section: Preparation Of Sol-particle Suspensionsmentioning
confidence: 99%
See 1 more Smart Citation